Organic photodetectors based on supramolecular nanostructures. (8th November 2020) - Yao, Yifan; Chen, Yusheng; Wang, Hanlin; Samorì, Paolo
Abstract: Self‐assembly of semiconducting (macro)molecules enables the development of materials with tailored‐made properties which could be used as active components for optoelectronics applications. Supramolecular nanostructures combine the merits of soft matter and crystalline materials: They are flexible yet highly crystalline, and they can be processed with low‐cost solution methods. Photodetectors are devices capable to convert a light input into an electrical signal. To achieve high photoresponse, the photogenerated charge carriers should be transported efficiently through the self‐assembled nanostructures to reach the electrodes; this can be guaranteed via optimal π–electron overlapping between adjacent conjugated molecules. Moreover, because of the high surface‐to‐bulk ratio, supramolecular nanostructures are prone to enhance exciton dissociation. These qualities make supramolecular nanostructures perfect platforms for photoelectric conversion. This review highlights the most enlightening recent strategies developed for the fabrication of high‐performance photodetectors based on supramolecular nanostructures. We introduce the key figure‐of‐merit parameters and working mechanisms of organic photodetectors based on single components and p–n heterojunctions. In particular, we describe new methods to devise unprecedented planar and vertical devices to ultimately realize highly integrated and flexible photodetectors. The incorporation of ordered mesoscopic supramolecular nanostructures into macroscopic optoelectronic devices will offer great promise for the next generation of multifunctional and multiresponsive devices. Abstract : Remarkable recent advances in organic photodetectors based on the supramolecular nanostructures from UV‐Vis to NIR, which have demonstrated the great promising. An overview of the most enlightening recent strategies developed for the fabrication of high‐performance self‐assembled organic optoelectronic devices is presented, by highlighting the challenges and opportunities toward the next generation of optoelectronic multifunctional and multiresponsive devices.